Anemia and micronutrient deficiencies in young children in urban slums of Mumbai, India - Fothergill, Amy; Huey, Samantha; Haas, Jere D.; Udipi, Shobha; Ghugre, Padmini; Thakker, Varsha (American Society for Nutrition, 2020)
To examine the burden of anemia and micronutrient deficiencies among young children living in urban slums of Mumbai, India.